Perakitan Varietas Padi Adaptif pada Tanah dengan Kandungan Fosfor Suboptimum - Hermanasari, Rini; Ardie, Sintho Wahyuning; Suwarno, Suwarno; Ghulamahdi, Munif; Aswidinnoor, Hajrial (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2017)
Adaptive rice varieties on P sub-optimum condition can be used by farmer to resolve the high macro fertilizer used, these varieties should be applied on rice field with P low input. Phosphor deficiency decreasing potentiality of result, therefore needs to develop rice promising lines that adaptive with P Sub-Optimum condition. The objective of this researched is to generate rice lines that adaptive on field with P sub-optimum condition and optimum through rice lines selection on the availability of difference P condition. The materials used are two population generation of F3, IR6008023/Bernas Prima and Gampai/Progol. The researched held at experiment station Muara, Bogor and Leuwiliang, West Java, started from April 2012 untill December 2014. F3 generation planted on P sub-optimum condition at Muara station, until obtained F4 and F5 population generations. Population of those two generations has been selected using bulk modification method and planted on environment conditions of P optimum (36 kg ha-1P₂O₅) and sub-optimum (without P fertilizer) so that generate F6 population generation. Rice lines 160 of F6 generation selected by panicle weight characteristic per hill. Those rice lines evaluated on two production environment, P optimum and P sub-optimum. Experiment on F6 generation was done using Augmented design. The result of the experiment shows that selection of bulk modification method effecive towards production environment of P optimum and P sub-optimum. The potential yield of promising rice lines more gained from Pop 1 population (IR6008023/ Bernas Prima), while tolarance on P sub-optimum condition gained from Pop 2 population (Gampai/Progol). 5 promising rice lines with high yield on P sub-optimum production environment are : B1451E-PS-40, B1451E-PS-21, B1452E-PS-48, B1452E-PS-43 and B1452E-PS-8, whereas rice lines with high yield on P optimum are: B1452E-PO-13, B1451E-PO-27, B1452E-PO-45, B1451E-PS-44 and B1452E-PO-8.